Anime & manga digital coloring guide : choose the colors that bring your drawings to life! - Sakurai, Teruko (Tuttle Publishing, an imprint of Periplus Editions (HK) Ltd, 2023)
"A colour science expert's must-have colouring guide for manga and anime artists! Author Teruko Sakurai, Japan's leading colourist, applies her expert knowledge of colour to drawing effective anime and manga. Starting with the basics, Sakurai shares her secrets on how to provide your characters and scenes with the right colours to accurately express their moods and actions. This all-in-one guide allows you to become a skilled colourist in just a few easy lessons. Here are just some of the key topics presented in this all-in-one handbook: How to select the right hair and eye colors to express the personality and mood of a character; The basics of coloru theory and how to match the colour palette of a scene with the story being told; Colour's role in conveying emotion - and the essential colours used to capture a particular mood; Hundreds of palette colour combinations and swatches with CMYK and RGB percentages-- all at your fingertips. This book shows you how to become a skilled digital colourist just by following a few simple guidelines--and how to refine your illustrations further using professional-level digital shading and coloration techniques. With hundreds of tips and sample palettes to refer to, Anime & Manga Digital Colouring Guide is a book every manga and anime artist will want to have!"--Publisher's description.